(untitled) (International Journal of Banking and Finance, 2010)
Islamic banking activities are limited within the scope of shari’ah which is within the scope of socially responsible and ethical banking activities, different from that based on interest-based banking. This paper attempts to measure the input data required by shari’ah-compliant banking in comparison with conventional banking to estimate their relative efficiencies and economies of and returns to scale. Cost and output distance functions were estimated for a sample of banks in 10 countries which operate both types of banking. The results showed that shari’ah-compliant banking has higher input requirements relative to interest based banking, but exhibit superior average efficiency only in Malaysia but inferior average efficiency in cross-country analysis. There is little evidence of differences in economies/returns to scale between shari’ah and conventional banks.